Low-dose cyclophosphamide combined with standard immunosuppressive therapy improves early response rates in severe aplastic anemia - Pan, Hong; Gao, Zhen; Zhang, Lele; Li, Weiwang; Li, Ruonan; Zhao, Jingyu; Yu, Xiao; Kuang, Zhexiang; Nie, Neng; Li, Jianping; Li, Yuan; Li, Xingxin; et al. (Frontiers in Immunology, 2026)
BackgroundThrombopoietin receptor agonists combined with anti-thymocyte globulin (ATG) and cyclosporine (CsA) are the standard immunosuppressive therapy (IST) for severe/very severe aplastic anemia (SAA/VSAA). However, early response rates remain suboptimal. Cyclophosphamide (CTX) has shown efficacy in relapsed/refractory AA. Therefore, we designed a clinical trial to evaluate low-dose CTX combined with the standard IST as a first-line treatment for SAA/VSAA to improve early response rates.MethodsThis study was a single-arm, prospective, phase II clinical trial using a Simon’s two-stage design, and 43 patients were enrolled. The primary endpoint was the overall response rate (ORR) at 3 months. Newly diagnosed SAA/VSAA patients received a combination treatment as follows: porcine ATG at 25 mg/kg/day from days 1 to 5, CsA at 3–5 mg/kg/day continuously, hetrombopag at 15 mg/day starting from day 1 and continued for 6 months, low-dose CTX at 20 mg/kg/day on days 29–30 and days 43-44.ResultsAll 43 patients achieved the primary endpoint, demonstrating 3-month and 6-month ORR of 65.1% (28/43) and 69.8% (30/43) respectively. Complete response (CR) rates were 9.3% (4/43) at 3-month and 27.9% (12/43) at 6-month. CTX associated toxicities comprised 100% grade 1–2 gastrointestinal reactions, grade 3–4 neutropenia in 62.8% of patients (median duration 6 days, range 4-33). Infectious events occurred in 60.5% (26/43) of patients within the first 3 months of treatment, while no mortality observed during this period.ConclusionsLow-dose CTX combined with standard IST appears to improve the early response rate in SAA/VSAA patients with manageable toxicity.